2022
DOI: 10.46747/cfp.6811836
|View full text |Cite
|
Sign up to set email alerts
|

Family physician practice patterns during COVID-19 and future intentions

Abstract: Objective To determine the extent to which family physicians closed their doors altogether or for in-person visits during the pandemic, their future practice intentions, and related factors.Design Cross-sectional survey.Setting Six geographic areas in Toronto, Ont, aligned with Ontario Health Team regions.Participants Family doctors practising office-based, comprehensive family medicine. Main outcome measuresPractice operations in January 2021, use of virtual care, and future plans. ResultsOf the 1016 (85.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…There was a higher proportion of physicians who worked alone in a clinic among those who did not see patients in person (27.6% no vs 12.4% yes, P<.01). 4 While most FPs kept their practices open, a second study from the same researchers published earlier this autumn showed a more worrisome pandemic trend 5 that was also supported by the current study. 4 Kiran et al found that about 3% of the more than 12,000 practising FPs in Ontario stopped working during the first 6 months of the pandemic-twice as many as in the previous decade.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…There was a higher proportion of physicians who worked alone in a clinic among those who did not see patients in person (27.6% no vs 12.4% yes, P<.01). 4 While most FPs kept their practices open, a second study from the same researchers published earlier this autumn showed a more worrisome pandemic trend 5 that was also supported by the current study. 4 Kiran et al found that about 3% of the more than 12,000 practising FPs in Ontario stopped working during the first 6 months of the pandemic-twice as many as in the previous decade.…”
supporting
confidence: 82%
“…4 While most FPs kept their practices open, a second study from the same researchers published earlier this autumn showed a more worrisome pandemic trend 5 that was also supported by the current study. 4 Kiran et al found that about 3% of the more than 12,000 practising FPs in Ontario stopped working during the first 6 months of the pandemic-twice as many as in the previous decade. Physicians stopping work were more likely to be aged 75 years or older, practise fee-for-service, have patient panel sizes under 500, and work less than other FPs in the previous year-factors that are likely correlated and consistent with FPs who are heading into retirement.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Fewer new family medicine graduates are choosing to pursue longitudinal family practice, 10,11 and more are leaving practice. 14 In an upcoming study of walk-in clinic physicians’ perspectives, scheduling flexibility, a desire to practice episodic care, the demand for walk-in care, and the fee-for-service payment model motivated the choice to practice in a walk-in setting. 65 Paradoxically, physician workforce diversion to walk-in clinics and other alternatives may further reduce access to longitudinal primary care, ensuring that demand for walk-in clinics remains high.…”
Section: Discussionmentioning
confidence: 99%
“…1013 In 2021, 1 in 5 family physicians in Toronto were considering closing their practices in the next 5 years, and only 5% indicated they were actively seeking to grow their practices. 14 Reasons for leaving practice included health concerns, financial pressures, burnout, retirement, and other work options in or outside of medicine. 1517 As a result, access to longitudinal primary care is likely to worsen in the coming decade.…”
Section: Introductionmentioning
confidence: 99%